KAJIAN DISTRIBUSI CURAH HUJAN PADA BEBERAPA STASIUN PENAKAR CURAH HUJAN DI DAS PADANG - Rodrik T Rodrik T; Kemala Sari Lubis; Supriadi Supriadi (Universitas Sumatera Utara, 2013)
This study was conducted to determine the frequency distribution of rainfall at Padang watershed.This research used descriptive statistic analysis by using rainfall data. Data’s used from nine station(Brohol, Pabatu, Kotarih, Silau Dunia, Gunung Para, Gunung Pamela, Gunung Monako, andMaligas) on 10 years. Suitability of pattern frequency distribution determined coefficient skewnessand kurtosis coefficients. The results show that the Gumbel distribution and Log Person Type IIImost suitable for distribution pattern of rainfall in the watershed Padang.